The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1063/1.5053424
|View full text |Cite
|
Sign up to set email alerts
|

Stability and electronic properties of planar defects in quaternary I2-II-IV-VI4 semiconductors

Abstract: Extended defects such as stacking faults and anti-site domain boundaries can perturb the band edges in Cu 2 ZnSnS 4 and Cu 2 ZnSnSe 4 , acting as a weak electron barrier or a source for electron capture, respectively. In order to find ways to prohibit the formation of planar defects, we investigated the effect of chemical substitution on the stability of the intrinsic stacking fault and metastable polytypes and analyze their electrical properties. Substitution of Ag for Cu makes stacking faults less stable, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…There are a number of studies focused on the defects in CZTS. It is difficult to characterize the behaviors of defects in semiconductors experimentally owing to low concentrations and optically dark nature of defects. Most of the theoretical studies of defects in CZTS mainly focus on the static properties, such as defect structure, defect level, and formation energy, electronic properties, and so on, and only a few of them have focused on the excited-state process . Sulfur vacancies result in n-type conductivity in CZTS and are dominant because of their low formation energy, although other elementary vacancies are also highly possible.…”
mentioning
confidence: 99%
“…There are a number of studies focused on the defects in CZTS. It is difficult to characterize the behaviors of defects in semiconductors experimentally owing to low concentrations and optically dark nature of defects. Most of the theoretical studies of defects in CZTS mainly focus on the static properties, such as defect structure, defect level, and formation energy, electronic properties, and so on, and only a few of them have focused on the excited-state process . Sulfur vacancies result in n-type conductivity in CZTS and are dominant because of their low formation energy, although other elementary vacancies are also highly possible.…”
mentioning
confidence: 99%
“…[9] Mitzi and Walsh's comparison between CZTS(Se) with CIGS solar cells concludes that the cells generate similar currents, but the limiting factors for CZTS are the open-circuit voltage deficit and point defects. [10][11][12][13][14][15][16] Computational modelling has been used to provide much of the band structure data for CZTS and CZTSe, however, a systematic steady and dynamic electrochemical analysis of CZTS and CZTSe, as well as what is their conductivity difference and electrochemical band alignment, is still lacking within the community. [17][18][19][20][21][22] Moreover, the electrochemical steady-state potential windows of CZTS and CZTSe provide important information about the limitations of various Net Zero applications, including solar cells, CO2 photoreduction, water splitting and lighting.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for materials with flat bands, a large k -point mesh is required. , It can be done with small computation power using local or semilocal functionals that are popularly used for high-throughput calculation studies. The prediction, however, can be very challenging using hybrid density functionals or GW approximations due to heavy computation costs. , The band edge positions predicted in local or semilocal calculation can be used as a good guess; however, this approach is not always correct because sometimes different band edge positions are predicted than the hybrid calculations. , These also predict many semiconductor materials as metals because of the band gap underestimation. The use of highly localized Wannier functions is another option to obtain the three-dimensional band structure; , however, it is sometimes quite difficult to achieve convergence. We recently have found that the total energy and the band gap of materials can be cost-effectively calculated using sparse k -point meshes for the Hartree–Fock exchange potential than the full k -point grid .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 These also predict many semiconductor materials as metals because of the band gap underestimation. The use of highly localized Wannier functions is another option to obtain the three-dimensional band structure; 20,21 however, it is sometimes quite difficult to achieve convergence. We recently have found that the total energy and the band gap of materials can be cost-effectively calculated using sparse k-point meshes for the Hartree−Fock exchange potential than the full k-point grid.…”
Section: ■ Introductionmentioning
confidence: 99%